2002
DOI: 10.1177/0954008302014001091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Polymers for Photoresist and Lithographic Printing Applications

Abstract: Lithographic resist materials based on copolymers and/or terpolymers have been synthesised. These materials are comprised of one component to induce water solubility, such as Nvinyl pyrrolidinone (NVP) or N, Ndimethyl acrylamide (DMAC); and another material to give the photoactive response, in this case allyl glycidyl ether (AGE) or glycidyl methacrylate (GMA). Copolymers and terpolymers of various compositions have been prepared by free radical copolymerization. Cationically initiated photocrosslinking was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The photoacid generator (MAS + –SbF 6 − ) was synthesized and characterized according to a previously published method 6–8, 22. As stated earlier, onium salt photoinitiators have found considerable use in photoresist chemistry for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photoacid generator (MAS + –SbF 6 − ) was synthesized and characterized according to a previously published method 6–8, 22. As stated earlier, onium salt photoinitiators have found considerable use in photoresist chemistry for a wide range of applications.…”
Section: Resultsmentioning
confidence: 99%
“…When the polymer resists are exposed to UV radiation, a strong acid is generated in the exposed regions as a result of the photochemistry of the photoacid generator (MAS + –SbF 6 − ). Upon PEB, the acid generated catalyzed the crosslinking of the resist polymer via an electrophilic attack of the pendant epoxide groups, thus rendering the exposed areas insoluble6–8, 22 as shown in Scheme .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] The high reactivity of the epoxide group is due to the considerable strain in the three-membered ring. The MAA monomer was chosen to provide water solubility.…”
Section: Poly(gma/maa/t-bocvp) Terpolymersmentioning
confidence: 99%
“…This reaction was explored further by Crivello who named these mixtures mixed aryl sulphonium (MAS) salts [10]. Further study has suggested that these mixtures contain more than 12 UV-absorbing components, which may play a part in the photoproduction of acidic species [11] The (MAS 3 -SbF 4 6 ) salt was made in a good yield as a white powder. The characteristic data for this material is presented in table 3.…”
Section: Synthesis and Evaluation Of Acrylate Copolymers 447mentioning
confidence: 99%